Gender, Perceived Discrimination and the Overruling of Roe v. Wade - Núria Rodríguez-Planas; Alan Secor (Institute of Labor Economics (IZA), 2025)
Have the recent changes in reproductive rights changed women's perceptions of discrimination and fair treatment relative to men's perceptions? To address this question, we collected online survey data (N=1,374) during spring 2023 using a randomized design that provided information about the enactment of State antiabortion laws and the overturning of Roe v. Wade by the U.S. Supreme Court to a treatment group but no information to an untreated control group. This exogenous variation in information dissemination was used to analyze perceived fairness and discrimination of treated individuals, by sex. We find that treatment increases women's overall perception of discrimination and unfair treatment in the US by 11.5 percent of a standard deviation and their perception relative to men by 21.8 percent of a standard deviation, widening an already existing gender gap. These results support the notion that the recent state and federal abortion restrictions can impact individuals' perceptions of fairness and discrimination in the U.S. and do so differentially by gender.
Keywords: J15; J16; I; K36; 330; perceived discrimination and fairness; gender; state and federal abortion restrictions; rights protection; randomized information treatment.